Essential elements of surgeon communication impacting patient satisfaction: a systematic review. (3rd April 2022) - O'Rorke, Erin V.; Mauch, Jaclyn T.; Liu, Yusha; Friedrich, Jeffrey B.
ABSTRACT: Background: While prior studies have emphasized the need for additional surgeon training on interpersonal and communication skills, current communication skills curricula is not guided by evidence correlating specific communication skills with patient satisfaction. To inform the maturation of this curricula, we performed a systematic review to examine the aspects of surgeon communication that have a positive impact on patient satisfaction. Methods: A qualitative literature review was conducted across four databases: PubMed, Embase, Scopus, and Ovid/Medline. Publications were included if the study both assessed surgeons' interpersonal/communication skills and correlated surgeon communication with patient satisfaction. Results: 26 publications met inclusion criteria and examined a broad range of physician specialties including urology, otolaryngology, and general, breast, vascular, and orthopedic surgery. These studies covered 654 surgeons, predominantly at the attending level, and 16, 538 patients. Three major themes were related to patient satisfaction: 1) clear communication, 2) involvement of the patient, and 3) demeanor and interpersonal skills. Specific skills that were associated with increased patient satisfaction include clearly defining care team roles, ensuring patient comprehension, setting expectations, utilizing surgeon-initiated and autonomy-supportive communication, practicing active listening, developing rapport, and providing culturally competent care. Conclusions: This systematic review demonstrates that clear surgeon communication, involvement of the patient in clinical decision-making, and demeanor and interpersonal skills are closely associated with patient satisfaction. Our findings present evidence-based recommendations for areas of improvement for practicing surgeons. Furthermore, surgical residency programs may focus their training efforts on development of these aspects of interpersonal and communication skills that directly impact patient satisfaction.